Guillain–Barre´ syndrome with bilateral facial palsy with incidental arachnoid cyst - Mondal, Monojit; Biswas, Biswajit; Roy, Atanu; Das, Rajib; Ghosh, Taraknath; Barik, Kanai Lal; Nayek, Kaustav; Datta, Asok Kumar (Asian Journal of Medical Sciences, 2015)
This case report describes the findings of a 10-year-old female child admitted with fever and headache for 3 days along with several episodes of vomiting and generalized seizures for 1 day. She regained consciousness 50 minutes after admission with initial treatment, but developed muscle weakness, followed by tetraplegia with areflexia, bilateral facial palsy and respiratory insufficiency. The nerve conduction study (NCV) had evidence of demyelinating neuropathy and the cerebrospinal fluid (CSF) showed albumin-cytological dissociation. These neurologic findings were consistent with the diagnosis of Guillain-Barré syndrome. The patient was treated with immunoglobulin and other supportive cares. Mechanical ventilation was started on day 3 of hospital admission in face of respiratory insuficiency. Recovery, however, was relatively quick and extubation was possible on 6th day. Work up for CNS infection was non-contributory. MRI of brain done during the course, revealed an archnoid cyst in right temporal region which might have contributed to the episode of unconsciousneess, vomiting and convulsion. After two weeks of hospitalization the patient was discharged from the hospital on wheel chair with satisfectory improvement of powers of facial and limb muscles. When the patient was seen at the outpatient department four weeks after hospital discharge, she was able to walk with help with normal facial nerve function on both sides. G B syndrome presenting like meningitis; bilateral facial palsy; and co-presence of an archnoid cyst makes this case worth sharing. DOI: http://dx.doi.org/10.3126/ajms.v6i5.11627 Asian Journal of Medical Sciences Vol.6(5) 2015 71-74